2014
DOI: 10.7897/2277-4343.056131
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Ayurvedic Management of Cerebral Palsy Affected Children

Abstract: Cerebral palsy (CP) is a common chronic motor disability among developmental disorder prevalent world widely among pediatric population. It is a group of condition characterized by motor dysfunction due to non progressive brain damage in its early developing period; often accompanied by other features like seizures, behavioral disorder, cognitive impairment and other secondary musculoskeletal problems restricting them from normal independency. The condition poses considerable therapeutic challenge to the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Vasti is most important Pradhan-karma to manage the Vata Dosha in treatment of Cerebral palsy. Short chain fatty acids of medicated oil reaches rectum, colon and direct diffusion property from epithelial cells to blood capillary where it shows generalized effect 48 . Vasti is restricted till the crawling age but Anuvasana vasti (oil enema) can be given from early infancy.…”
Section: • Matra-vasti (Oil Enema In Small Dose)mentioning
confidence: 99%
“…Vasti is most important Pradhan-karma to manage the Vata Dosha in treatment of Cerebral palsy. Short chain fatty acids of medicated oil reaches rectum, colon and direct diffusion property from epithelial cells to blood capillary where it shows generalized effect 48 . Vasti is restricted till the crawling age but Anuvasana vasti (oil enema) can be given from early infancy.…”
Section: • Matra-vasti (Oil Enema In Small Dose)mentioning
confidence: 99%
“…Various panchakarma procedures like Udwartana (medicated powder massage), Sarvaanga abhyanga (full body massage with medicated oil), Baashpa sweda & Naadi sweda (steam bath), Shashtika shali pinda sweda -SSPS (sudation with a bolus prepared by boiled rice), Nasya, Shirodhara (oil drip over the forehead) and Vasti (oil and decoction enemas), are found to be beneficial in the management of CP. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Present study is focused only on few panchakarma procedures which are commonly used and found effective in the management of CP like Udwartana, Sarvaanga abhyanga, Baashpa sweda & Naadi sweda, Shashtika shali pinda sweda, Nasya and Vasti.…”
Section: Some Effective Panchakarma In Cpmentioning
confidence: 99%
“…Abhyanga and SSPS both cumulatively help in reduction of spasticity and facilitate free movement of joint preventing from deformities and contractures in CP cases. 17 Massage of the entire body with medicated oils like Bala tailam, Narayana tailam, Prasarini tailam, and Mashadi tailam are very effective. Massage involving concomitant stretching maneuvers is very beneficial in patients with spastic diplegia resulting from CP.…”
Section: Sarvaanga Abhyangamentioning
confidence: 99%
See 1 more Smart Citation
“…Often accompanied by other features like seizure behavioural disorder, cognitive impairment and other musculoskeletal problem 1 . It is a most common physical disability in early childhood.…”
Section: Introductionmentioning
confidence: 99%